(untitled) (Revista Educação, Artes e Inclusão, 2020)
This is an article deriving from a research-montage based on traces found in the city of Porto Alegre (RS), between 2017 and 2018. Such traces are composed of urban writings captured during the course of the research in street walls, as well as floor findings, besides fragments of writing that were produced as a result of the researchers’ encounter with the materials. Assuming what we called a book method, and assuming as methodological intercessor Julio Cortázar’s Hopscotch (Rayuela), a text is traced with the images found on the streets. The cartographic narratives of the displacements around the city inspire ways of saying, feel and look at the multiple urban landscapes that hide and also reveal themselves in the encounter with a city, in a movement operated by what is called “Writewith”. The article ends in an essayistic manner with the writing of a manifest by the book method, where some premises are signaled to those who may also be interested in this.